Development of an advanced nano-satellite (VELOX-II) onboard computer system - Chan, Pak Lam (2015)
VELOX-II is an advanced satellite weighing 12 kg and is presently built by NTU’s satellite research centre (SaRC). The satellite is classified as a nano-satellite. VELOX-II is expected to be completed and ready for launch in last quarter of 2015. The satellite will be launched into the near equatorial orbit at an altitude of 550km. This final year project focuses on the development of data compression system for the onboard computer system. The objective of this to develop an automated data compression algorithm testing software in order to assist in finding the most appropriate data compression algorithm to be used in VELOX-II. Currently, VELOX-II’s onboard computer system has several systems implemented successfully in the areas such as error-correction, onboard data-handling and cryptography. However the data compression system has not yet been explored. A suitable data compression system will reduce satellite’s transmission time, disk space for data storage as well as bandwidth for transmission. This will be very essential for VELOX-II application as it has only about VELOX-II has approximately 150 minutes to transfer data to the ground station for each day. It also means 1290 minutes VELOX-II is not transmitting any data per day. This idle time can be used for data compression. This project consists of two stages: First stage is to develop an automated data compression testing window form application and implement all the well-known compression algorithms. Subsequently in the second stage, we will analyze and decide the best algorithm for VELOX-II’s application. Automated data compression testing window form application has been successfully developed. The compression algorithms that were tested using the applications are: Run length encoding, LZ77 code, Shannon-Fano code, Huffman code, Rice code. These algorithms are some of the most popular data compression algorithm which can be used directly or integrated to a more advanced algorithms. The application has the capability to transport raw data into a text file which can be easily copied by user to the Microsoft Excel sheet. After this operation, user can effortlessly do graphical and statistical analysis using standard Excel functions on the compression performances. After analyzing VELOX-PII’s data, an operational pico satellite which collects similar data as VELOX-II, Lempel-Ziv (fast) was concluded to be the best algorithm for application due to several reasons: low compression percentage (68.28%), high decompression speed (235183 kB/s). Despite Lempel-Ziv (fast) has slower compression speed (2992 kB/s) in comparison to other tested algorithms, it was calculated to be suffice for VELOX-II’s application as it has 13 times more allowance than the projected requirement for VELOX-II’s application. It is projected to transmit 675000 byte worth of data per day. When Lempel-Ziv (fast) compression algorithm is implemented successfully on both onboard computer and ground station, using the idle time to compress data, system will benefit from lesser disk space for data storage, lesser bandwidth for data transmission and lesser time for data transmission.